Diabetic hip arthropathy is associated with a higher prevalence of femoral head chondromalacia: a case-controlled study. Issue 5 (September 2019) - Luo, T David; Marquez-Lara, Alejandro; Stone, Austin V; Mannava, Sandeep; Howse, Elizabeth A; Rosas, Samuel; Schallmo, Michael S; Atilla, H Atil; Stubbs, Allston J
Introduction: No previous studies have characterised hip joint disease in diabetic patients undergoing hip arthroscopy. The purpose of our study was to evaluate intra-articular hip pathology and surgical variables in patients with diabetes compared to matched, non-diabetic controls. We hypothesised that diabetic patients would demonstrate a higher prevalence and severity of hip chondral pathology. Methods: We retrospectively reviewed 795 consecutive hip arthroscopies performed by a single surgeon between 2010 and 2015. Patients ⩾18 years of age without a history of diabetes served as controls and were matched based on age, sex, body mass index, duration of symptoms, and operative side. Clinical symptoms, preoperative physical examination, and radiologic and intraoperative findings were assessed. The primary outcomes were the acetabular and femoral head chondromalacia index (CMI), calculated as the product of the Outerbridge chondromalacia grade and surface area (mm 2 *severity). Results: 15 diabetic patients were matched to 137 non-diabetic controls. Diabetic patients demonstrated a higher prevalence of femoral head chondromalacia compared to controls both on magnetic resonance imaging (45.5% vs. 7.5%, p = 0.002) and during arthroscopy (100% vs. 75.9%, p = 0.042). Femoral head chondromalacia in diabetic patients had higher Outerbridge grade (2.4 vs. 2.0, p = 0.030) but similar CMI (513.0 vs. 416.4, p = 0.298) compared to controls. Discussion: Femoral head chondral pathology was more prevalent and of higher severity grade in diabetic patients. The prevalence, size, and severity of acetabular chondral disease were similar between diabetic and non-diabetic patients. Multivariate analysis demonstrated that diabetic status was independently associated with the presence of femoral head chondromalacia.